A Simple Heliodon System for Horizontal Placed Models - Maged G Mikhael; Mostafa Metwaly (Alanya Hamdullah Emin Paşa Üniversitesi, 2017)
Most probably, all our buildings are affected by sunlight. Hence, the ignorance of the sun’s impact results in overheating, glare, and missed opportunities for the positive use of daylight, leading to wasted energy. Heliodon is considered to be a powerful tool that can aid students, professionals, building developers and users to better understand the relationship between the sun’s path and its effects on the architectural model(s). Most of the heliodons are relatively expensive and complex in operation. Thus, the need to design and build a simple and relatively inexpensive one emerged. It was proposed to work on this heliodon as a team project in the environmental control class “fall-2016”. The authors put the design concept and introduced a mathematical calculations table to be used with the physical heliodon, while nine students participated in the manufacturing process. The design concept is based on determining the sun’s position by converting the Altitude and Azimuth angels to their corresponding measurements on the (X, Y & Z) coordinates (in relation to the observer’s location). One light source can be moved on a set of graded tubes assembled in the shape of a wireframe box (thus the X, Y & Z distances could be measured) to simulate the sun’s position and its lighting conditions for any latitude, at any time for any chosen day.